A little trouble in Amsterdam - MacAndrew, Richard (United Kingdom Cambridge University Press, 2009)
" Mary what are you doing ? We can't go in here. This is someone's house." Sometimes he couldn't believe the things his sister did. She was always getting them into trouble- and he usually had to get them out.
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents.
Keywords: Language Learning; Elementary/lower-intermediate level; Reading books; Adventure